Experimental studies on pollenmediated gene flow in Sorghum bicolor (L.) Moench using malesterile bait plants - Rabbi, Ismail Y.; Parzies, H.K.; Kiambi, D.; Haussmann, B.I.G.; Folkertsma, R.T.; Geiger, H.H (Wiley, 2011)
Information on the potential of pollen mediated gene flow (PMGF) in sorghum is required for ensuring varietal purity and to mitigate risk transgenic gene flow. Replicated trials were conducted in Kenya using a local landrace, ‘Ochuti’ as pollen donor surrounded by male-sterile pollen baits. Frequency of PMGF decreased with the increase of distance from pollen sources and was significantly influenced by wind direction and speed. Anther dehiscence correlated with increase in vapour pressure deficit in the morning. A negative exponential regression model with logarithmic transformation of PMGF and square-root transformation of distance from source field best fitted the data. Up to 50% of female florets on a male sterile (MS) plant were pollinated at 1 m from pollen source and declined to 14% at 10 m. The maximum distance of PMGF using the PMGF model, based on a threshold of one seed per MS plant, was 203 m when data above the 95th percentile is considered. However, in the presence of self-produced pollen of male-fertile target plants, the possibility of long-distance cross-pollination may be very low.